Entrepreneurial Behavior in Organizations: Does Job Design Matter? - de Jong, J.; Parker, Sharon; Wennekers, S.; Wu, C. (2015)
We take a first step to explore how organizational factors influence individual entrepreneurial behavior at work, by investigating the role of job design variables. Drawing on multiple-source survey data of 179 workers in a Dutch research and consultancy organization, we find that entrepreneurial behavior, indicated by innovation, proactivity, and risk-taking items, is a higher order construct. Job autonomy is positively related with entrepreneurial behavior, as well as its innovation and proactivity subdimensions, while job variety is not. This suggests that interventions related to the vertical scope of jobs will promote entrepreneurial behaviors more than horizontal job expansion.